Do rising top incomes lift all boats? - Dan Andrews; Christopher Jencks; Andrew Leigh (Institute for the Study of Labor (IZA), 2010)
Pooling data for 1905 to 2000, we find no systematic relationship between top income shares and economic growth in a panel of 12 developed nations observed for between 22 and 85 years. After 1960, however, a one percentage point rise in the top decile's income share is associated with a statistically significant 0.12 point rise in GDP growth during the following year. This relationship is not driven by changes in either educational attainment or top tax rates. If the increase in inequality is permanent, the increase in growth appears to be permanent. However, our estimates imply that it would take 13 years for the cumulative positive effect of faster growth on the mean income of the bottom nine deciles to offset the negative effect of reducing their share of total income.
Keywords: D31; N10; O57; 330; Inequality; growth; income distribution; national income; Einkommensverteilung; Soziale Ungleichheit; Reichtum; Wirtschaftswachstum; Verteilungswirkung; Industriestaaten